Study of Unstimulated Salivary Flow rate and pH Before and After Partial and Complete Removable Denture Wearers - Dr. Mohammad Bashir Nejabi; Dr. Amina Ghuriani; Dawlaty, Dr.Brishna (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2020)
Back ground and aim: Among the main functions of saliva, lubricant activity maintains the tissue integrity and provide adhesion and cohesion that lead to effective denture retention. In addition, normal salivary flow maintains pH of oral cavity. Beside these Unstimulated whole salivary flow rate best describes the status of oral cavity. Therefore, in this study both Salivary flow rate and pH of saliva was investigated before and after one month of partial and complete denture placement. Material and method: this study was conducted on 25 volunteer participants with 68% female and 32% male. From all samples 72% were partial removable denture and 28% were complete removable denture wearers. Salivary flow rate was calculated according to volume collected per collection time and pH was determined by digital pH meter. For comparing salivary flow rate and pH before and after removable denture placement, paired sample test was performed. Result: In this study 17 female and 8 males with mean age of 48 years old were participated Mean salivary flow rate before and after wearing denture were0.84±0.037 and 0.98±0.037 respectively that was statistically significant. But differences in Salivary pH before and after denture wear were not significant. There was no Correlation of age, gender and pH on salivary flow rate before and after denture wear. There was positive correlation between salivary flow rate before and after partial removable denture placement.